Composition, porous membrane, porous membrane with base material

JP2025034735APending Publication Date: 2025-03-13SUMITOMO OSAKA CEMENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023141308
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-31
Publication Date
2025-03-13

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、基材への密着性に優れ、かつ残炭の含有量が少ない多孔質膜を形成することができる組成物、その組成物の成膜体である多孔質膜、および、前記多孔質膜を有する基材付き多孔質膜、並びに、組成物の製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025034735000001
    Figure 2025034735000001
  • Figure 2025034735000002
    Figure 2025034735000002
  • Figure 2025034735000003
    Figure 2025034735000003
Patent Text Reader

Abstract

To provide: a composition capable of forming a porous membrane excellent in adhesion to a base material and having a low content of residual carbon; the porous membrane formed from the composition; a porous membrane with the base material having the porous membrane; and a method for producing the composition.SOLUTION: A composition comprises: ceramic particles α having a primary particle diameter of less than 10 nm; ceramic particles β having a primary particle diameter of 10 nm or more; carboxylic acid having a carbon number of less than 5; a binder; and an organic solvent. A ratio (ceramic particle β / ceramic particle α) of the ceramic particle β to the ceramic particle α is 1 or more and 20 or less by mass ratio, and an average primary particle diameter of the ceramic particle β is 20 nm or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composition, a porous membrane which is a membrane formed from the composition, and a substrate-attached porous membrane having the porous membrane. [Background technology]

[0002] Porous membranes are widely used in the home, for example as deodorants or desiccants, and in industrial applications, for example as membranes for separating substances.

[0003] Patent Document 1 describes a separation membrane element including a porous molded body and a porous membrane. Patent Document 1 also describes a composition for forming a porous membrane, which contains an inorganic sol (fine particles (particle 1) of about 20 nm), mineral particles (large particles (particle 2) of 300 nm to 10 μm), a binder, and water, and has a mass ratio of particle 2 to particle 1 (particle 2 / particle 1) of 2.5 to 20.

[0004] Patent Document 2 describes a composition for forming a porous membrane, which contains ceramic sol particles (particle 1) of 5 to 50 nm, ceramic particles (particle 2) of 500 nm to 1000 nm, a binder, and water, and in which the ratio of particle 2 to particle 1 (particle 2 / particle 1) is 3.3 or more and 100 or less by mass. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 63-274407 [Patent Document 2] Japanese Patent Application Publication No. 10-235172 Summary of the Invention [Problem to be solved by the invention]

[0006] However, the porous film formed using the composition described in Patent Document 1 and the composition described in Patent Document 2 has a problem of poor adhesion to the substrate. In addition, in Patent Document 1, a surfactant is added to improve wettability to the substrate, and this surfactant remains as carbon after heat treatment, which causes a problem of deteriorating electrical and mechanical properties.

[0007] The present invention has been made in consideration of the above circumstances, and aims to provide a composition capable of forming a porous film having excellent adhesion to a substrate and a low residual carbon content, a porous film formed from the composition, a substrate-attached porous film having the porous film, and a method for producing the composition. [Means for solving the problem]

[0008] The present invention has the following aspects. [1] Ceramic particles α having a primary particle size of less than 10 nm; Ceramic particles β having a primary particle size of 10 nm or more; a carboxylic acid having less than 5 carbon atoms; Binder and an organic solvent, a ratio of the ceramic particles β to the ceramic particles α (ceramic particles β / ceramic particles α) is, in terms of mass ratio, 1 or more and 20 or less; The composition, wherein the ceramic particles β have an average primary particle size of 20 nm or more. [2] The composition described in [1], having a water content of 1% by mass or less. [3] The composition according to [1] or [2], wherein the ceramic particles α and the ceramic particles β are an oxide containing zirconium. [4] A porous film which is a film formed from the composition according to any one of [1] to [3]. [5] The porous membrane according to [4], having a porosity of 30% or more and a residual carbon content of less than 1 mass%. [6] A substrate; A porous membrane provided on at least one surface of the substrate, The porous membrane is a substrate-attached porous membrane according to [4] or [5]. [7] A method for producing the composition according to any one of [1] to [3], A step of dispersing a mixed liquid containing ceramic particles A1 having an average primary particle size of 1 nm or more and less than 10 nM, a carboxylic acid having a carbon number of less than 5, and a dispersion medium to prepare a dispersion A2 having an average secondary particle size of 1 nm or more and 10 nm or less; A step of preparing a dispersion liquid B2 by dispersing a mixed liquid containing ceramic particles B1 having an average primary particle size of 20 nm or more, a binder, and a dispersion medium; preparing a composition by mixing the dispersion A2 and the dispersion B2 in a mass ratio of the ceramic particles B1 to the ceramic particles A1 (ceramic particles B1 / ceramic particles A1) of 1 or more and 20 or less, A method for producing a composition, wherein a value obtained by dividing an average secondary particle size of the dispersion liquid B2 by an average primary particle size of the ceramic particles B1 is 1 or more and 10 or less. Effect of the Invention

[0009] According to the present invention, it is possible to provide a composition capable of forming a porous film having excellent adhesion to a substrate and a low residual carbon content, a porous film formed from the composition, a substrate-attached porous film having the porous film, and a method for producing the composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The embodiments of the composition, the porous membrane, the substrate-attached porous membrane, and the method for producing the composition of the present invention will be described below. It should be noted that the present embodiment is specifically described to allow a better understanding of the gist of the invention, and does not limit the present invention unless otherwise specified.

[0011] [Composition] A composition according to one embodiment of the present invention includes ceramic particles α having a primary particle diameter of less than 10 nm, ceramic particles β having a primary particle diameter of 10 nm or more, a carboxylic acid having less than 5 carbon atoms, a binder, and an organic solvent. In addition, in the composition according to one embodiment of the present invention, the ratio of the ceramic particles β to the ceramic particles α (ceramic particles β / ceramic particles α) is, in terms of mass ratio, 1 or more and 20 or less. In addition, in the composition according to one embodiment of the present invention, the average primary particle diameter of the ceramic particles β is 20 nm or more.

[0012] "Ceramic particles α, ceramic particles β" The ceramic particles α are not particularly limited as long as the primary particle diameter is less than 10 nm, and examples thereof include alumina (Al2O3), lead zirconate titanate (PZT), barium titanate (BaTiO3), zirconium oxide (ZrO2), etc. Among these, from the viewpoint of chemical stability, the ceramic particles α are preferably an oxide containing zirconium, and more preferably zirconium oxide.

[0013] The ceramic particles α have a primary particle diameter of less than 10 nm, preferably less than 8 nm, and more preferably less than 5 nm. The lower limit of the primary particle diameter of the ceramic particles α may be 1 nm or more, 2 nm or more, or 3 nm or more. The ceramic particles α having a primary particle diameter of less than 10 nm can enter the gaps between the ceramic particles β having an average primary particle diameter of 20 nm or more by the manufacturing method described later. Therefore, the binding property between the ceramic particles is improved, and the adhesion property between the substrate and the porous film described later can be improved.

[0014] The primary particle size of the ceramic particles α can be measured by measuring the major axis of the ceramic particles α using a transmission electron microscope, or by converting the specific surface area obtained by a gas adsorption surface area measurement method. The average primary particle size of the ceramic particles α can be calculated, for example, by the arithmetic average of the major axes of 100 ceramic particles α using a transmission electron microscope. The primary particle size of the ceramic particles α in the composition of this embodiment can be measured by observing the composition with a transmission electron microscope. When the composition of the present embodiment is produced by the production method described below, the primary particle diameter of the ceramic particles α is the same as the primary particle diameter of the ceramic particles α in the composition. Therefore, the primary particle diameter of the ceramic particles α itself may be taken as the primary particle diameter of the ceramic particles α in the composition.

[0015] The ceramic particles β are not particularly limited as long as they have a primary particle diameter of 10 nm or more and an average primary particle diameter of 20 nm or more, and examples thereof include alumina (Al2O3), lead zirconate titanate (PZT), barium titanate (BaTiO3), zirconium oxide (ZrO2), etc. Among these, from the viewpoint of chemical stability, the ceramic particles β are preferably oxides containing zirconium, and more preferably zirconium oxide.

[0016] The ceramic particles β have a primary particle diameter of 10 nm or more, preferably 20 nm or more, and more preferably 40 nm or more. The upper limit of the primary particle diameter of the ceramic particles β may be 10 μm or less, 1 μm or less, 500 nm or less, or 100 nm or less. The ceramic particles β have an average primary particle size of 20 nm or more, preferably 30 nm or more, and more preferably 40 nm or more. The upper limit of the average primary particle size of the ceramic particles β may be any value that provides adhesion to the substrate, and may be, for example, 10 μm or less, 1 μm or less, 500 nm or less, or 100 nm or less.

[0017] The primary particle size and average primary particle size of the ceramic particles β can be measured in the same manner as the primary particle size and average primary particle size of the ceramic particles α.

[0018] In the composition of this embodiment, the ratio of ceramic particles β to ceramic particles α (ceramic particles β / ceramic particles α) is, in mass ratio, from 1 to 20, preferably from 2 to 10, and more preferably from 3 to 7. If the ratio is less than the lower limit, the porous film may crack due to shrinkage caused by the ceramic particles α when the composition is formed into a film and then heat-treated. If the ratio exceeds the upper limit, the binding property of the ceramic particles α is insufficient, and the strength of the porous film decreases.

[0019] In the composition of the present embodiment, the ceramic particles α and β may be surface-modified in order to increase the affinity of the ceramic particles α and β with the organic solvent. The surface modifier is not particularly limited as long as it has a functional group that adsorbs to the surface of the ceramic particles α and β and has an end group that has affinity with the organic solvent, and examples of the surface modifier include 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, cysteamine, tetramethylammonium hydroxide, and aminoethanediol.

[0020] In the composition of this embodiment, the contents of the ceramic particles α and the ceramic particles β are not particularly limited as long as the ratio of the ceramic particles β to the ceramic particles α is 1 or more and 20 or less and a coating film can be formed. For example, the content of the ceramic particles α may be from 0.1% by mass to 20% by mass, from 0.5% by mass to 15% by mass, or from 0.8% by mass to 10% by mass. For example, the content of ceramic particles β may be 1 mass% or more and 50 mass% or less, 3 mass% or more and 40 mass% or less, 5 mass% or more and 30 mass% or less, or 5 mass% or more and 20 mass% or less.

[0021] "Carboxylic acid" The composition of the present embodiment contains a carboxylic acid having a carbon number of less than 5. By containing a carboxylic acid having a carbon number of less than 5, the dispersibility of the ceramic particles α in the composition can be maintained, and the amount of carbon residue when a porous film is formed can be reduced. Examples of carboxylic acids having less than 5 carbon atoms include formic acid, acetic acid, propionic acid, isobutyric acid, and butyric acid. Among these, acetic acid is preferred from the viewpoint of ease of handling of the composition, such as toxicity and odor. Note that "carboxylic acid having less than 5 carbon atoms" has the same meaning as "carboxylic acid having 4 or less carbon atoms."

[0022] In the composition of the present embodiment, the content of the carboxylic acid having less than 5 carbon atoms is preferably 0.1 mass% or more. By having the content of the carboxylic acid having less than 5 carbon atoms be 0.1 mass% or more, the dispersibility of the ceramic particles α in the composition is maintained, allowing the ceramic particles α to be uniformly present in the composition, and allowing the ceramic particles α to exert a binding force in the porous film. The upper limit of the content of carboxylic acids having less than 5 carbon atoms is not particularly limited as long as the dispersibility of ceramic particles α is maintained, and may be 10 mass% or less, 5 mass% or less, 3 mass% or less, or 1 mass% or less.

[0023] "binder" In this embodiment, the binder contributes to adjusting the viscosity of the composition and forming voids when the composition is made into a porous film. The binder is not particularly limited as long as it is substantially completely decomposed, burned or evaporated at or below the heat treatment temperature at which the composition is formed into a film and then heat-treated, and examples thereof include ethyl cellulose, polyacrylic acid ester, polymethacrylic acid ester, acrylic-modified ethyl cellulose, methacrylic-modified ethyl cellulose, etc. Among these, ethyl cellulose is preferred from the viewpoint of viscosity controllability of the composition.

[0024] In the composition of the present embodiment, the binder content is preferably 0.1% by mass or more and 40% by mass or less, more preferably 1% by mass or more and 35% by mass or less, even more preferably 8% by mass or more and 30% by mass or less, and even more preferably 14% by mass or more and 25% by mass or less. If the binder content is above the lower limit, voids are generated in the film formed from the composition and heat-treated. If the binder content is below the upper limit, the ceramic particles in the porous film are bonded to each other, improving the strength of the porous film.

[0025] "Organic solvents" The organic solvent is not particularly limited as long as it has affinity with the ceramic particles α and the ceramic particles β and dissolves the binder, but examples thereof include alcohols such as methanol, ethanol, 1-propanol, 2-propanol, diacetone alcohol, furfuryl alcohol, ethylene glycol, hexylene glycol, and terpineol, esters such as methyl acetate and ethyl acetate, ethers such as diethyl ether, ethylene glycol monomethyl ether (methyl cellosolve), ethylene glycol monoethyl ether (ethyl cellosolve), ethylene glycol monobutyl ether (butyl cellosolve), diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, dioxane, and tetrahydrofuran, ketones such as acetone, methyl ethyl ketone, acetylacetone, and acetoacetate, acid amides such as N,N-dimethylformamide, and aromatic hydrocarbons such as toluene and xylene. One of these organic solvents may be used alone, or two or more may be mixed together. Among these organic solvents, terpineol is preferred from the viewpoint of ease of handling. The composition of the present embodiment uses an organic solvent as a dispersion medium, and therefore has excellent wettability to the substrate described below, and can improve the adhesion between the substrate and the porous film.

[0026] In the composition of the present embodiment, the content of the organic solvent may be the remainder of other components. For example, the content of the organic solvent may be 50% by mass or more and 90% by mass or less, 60% by mass or more and 85% by mass or less, or 65% by mass or more and 80% by mass or less. By having the content of the organic solvent in the above range, the ceramic particles α and the ceramic particles β can be uniformly mixed, and the composition can be uniformly applied to the substrate.

[0027] The composition of the present embodiment may contain surfactants, preservatives, stabilizers, defoamers, leveling agents, etc., as appropriate, in order to ensure the dispersion stability of the ceramic particles α and ceramic particles β in the organic solvent and to improve the coating properties, as long as the purpose of the present invention is not hindered. In order to reduce the content of residual carbon, it is preferable not to contain a surfactant. These can be appropriately selected so that the average secondary particle size of the ceramic particles α and ceramic particles β in the dispersion liquid or composition described below and the viscosity of the composition are within the desired range.

[0028] In the composition of the present embodiment, the contents of the above-mentioned surfactants, preservatives, stabilizers, defoamers, leveling agents, etc. are not particularly limited, and may be set to a range according to the application of the composition, etc., so that the viscosity of the composition and the average secondary particle diameters of the ceramic particles α and ceramic particles β in the dispersion liquid or composition described below are within the desired ranges.

[0029] From the viewpoint of easily forming a coating film, the viscosity of the composition of this embodiment is preferably 100 Pa·s or more and 2000 Pa·s or less, more preferably 300 Pa·s or more and 1700 Pa·s or less, and even more preferably 500 Pa·s or more and 1500 Pa·s or less. The viscosity of the composition of the present embodiment means the value measured with a viscometer at room temperature (25° C.) and at a shear rate of 1 s −1 .

[0030] The composition of the present embodiment is obtained by the manufacturing method described below, so that the ceramic particles α can be uniformly present in the gaps between the ceramic particles β. Therefore, when the composition of the present embodiment is made into a porous film, it has excellent adhesion to a substrate.

[0031] "Method of producing the composition" A method for producing the composition of this embodiment will be described. The method for producing the composition of the present embodiment is the method for producing the composition of the above-mentioned embodiment, and includes the steps of dispersing a mixed liquid containing ceramic particles A1 having an average primary particle diameter of 1 nm or more and less than 10 nN, a carboxylic acid having less than 5 carbon atoms, and a dispersion medium to produce a dispersion liquid A2 having an average secondary particle diameter of 1 nm or more and 10 nm or less, dispersing a mixed liquid containing ceramic particles B1 having an average primary particle diameter of 20 nm or more, a binder, and a dispersion medium to produce a dispersion liquid B2, and mixing the dispersion liquid A2 and the dispersion liquid B2 in a mass ratio of the ceramic particles B1 to the ceramic particles A1 (ceramic particles B1 / ceramic particles A1) of 1 or more and 20 or less to produce a composition, and a value obtained by dividing the average secondary particle diameter of the dispersion liquid B2 by the average primary particle diameter of the ceramic particles B1 is 1 or more and 10 or less.

[0032] "Step of preparing dispersion A2" In this process, a mixture containing ceramic particles A1 having an average primary particle diameter of 1 nm or more and less than 10 nm, a carboxylic acid having a carbon number of less than 5, and a dispersion medium is dispersed until the average secondary particle diameter of the ceramic particles A1 becomes 1 nm or more and 10 nm or less, to produce dispersion A2. The particle diameter of the ceramic particles A1 may be the same as that of the ceramic particles α, or the ceramic particles A1 may be composed of only particles having a primary particle diameter of less than 10 nm, or may be composed of only particles having a primary particle diameter of less than 5 nm. That is, in this process, a mixture containing ceramic particles α having a primary particle diameter of less than 10 nm, a carboxylic acid having a carbon number of less than 5, and a dispersion medium may be dispersed until the average secondary particle diameter of the ceramic particles α is 1 nm or more and 10 nm or less, to prepare dispersion liquid A2. The particle diameter of the ceramic particles A1 may be the same as that of the ceramic particles α, but as long as the ratio of ceramic particles β / ceramic particles α in the composition is 1 or more and 20 or less, the ceramic particles A1 may contain particles with a primary particle diameter of 5 nm or more or 10 nm or more.

[0033] The average primary particle size of the ceramic particles A1 is 1 nm or more and less than 10 nm, preferably 2 nm or more and less than 8 nm, and more preferably 3 nm or more and less than 5 nm. The content of ceramic particles A1 in dispersion liquid A2 is not particularly limited as long as the ceramic particles A1 can be dispersed in the amount, and may be, for example, 1% by mass or more and 50% by mass or less, 5% by mass or more and 40% by mass or less, or 10% by mass or more and 30% by mass or less.

[0034] The carboxylic acid having less than 5 carbon atoms can be the same as that described above. The content of carboxylic acid in dispersion liquid A2 is not particularly limited as long as the average secondary particle diameter of ceramic particles A1 can be made to be 1 nm or more and 10 nm or less, and may be, for example, 0.1 mass % or more and 10 mass % or less, or 1 mass % or more and 8 mass % or less. The average secondary particle diameter of the ceramic particles A1 in this embodiment means a value (D50) when the cumulative volume percentage of the particle size distribution measured by a particle size distribution meter for the dispersion A2 is 50%. The particle size distribution may be measured in a dispersion in which the content of the ceramic particles A1 is adjusted to 1 mass %. The value (D50 / D90) obtained by dividing D50 by the value (D90) when the cumulative volume percentage of the particle size distribution is 90% is preferably 0.4 to 1, more preferably 0.5 to 1, and more preferably 0.6 to 1. When D50 / D90 is 0.4 or more, the ceramic particles A1 (ceramic particles α) can be uniformly present in the gaps between the ceramic particles B1 (ceramic particles β).

[0035] The dispersion medium is not particularly limited as long as it has a high affinity with the ceramic particles A1 and a carboxylic acid having less than 5 carbon atoms, and examples thereof include water, methanol, ethanol, 1-propanol, 2-propanol, diacetone alcohol, furfuryl alcohol, ethylene glycol, hexylene glycol, terpineol, and other alcohols, methyl acetate, ethyl acetate, and other esters, diethyl ether, ethylene glycol monomethyl ether (methyl cellosolve), ethylene glycol monoethyl ether (ethyl cellosolve), ethylene glycol monobutyl ether (butyl cellosolve), diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, dioxane, tetrahydrofuran, and other ethers, acetone, methyl ethyl ketone, acetylacetone, acetoacetate, and other ketones, N,N-dimethylformamide, and other acid amides, and toluene, xylene, and other aromatic hydrocarbons. Among these, water is preferred from the viewpoint of its high affinity with a carboxylic acid having less than 5 carbon atoms. The content of the dispersion medium can be the remainder of other components.

[0036] The method for dispersing the ceramic particles A1 (ceramic particles α) in the dispersion medium is not particularly limited, but for example, a wet method is preferable. In addition, as a dispersing machine used in this wet method, either an open type or a closed type can be used, and for example, a ball mill, an agitating mill, a jet mill, a vibration mill, an attritor, a high-speed mill, a hammer mill, etc. are preferably used. The ball mill may be a tumbling mill, a vibration mill, a planetary mill, etc., and the stirring mill may be a tower mill, a stirring tank mill, a flow tube mill, a tubular mill, etc.

[0037] "Step of preparing dispersion B2" In this step, a mixture containing ceramic particles B1 having an average primary particle size of 20 nm or more, a binder, and a dispersion medium is dispersed to produce a dispersion B2. The dispersion is performed until the value obtained by dividing the average secondary particle size of the ceramic particles B1 by the average primary particle size of the ceramic particles B1 is 1 to 10.

[0038] The particle diameter of the ceramic particles B1 may be the same as that of the ceramic particles β, or the ceramic particles B1 may be composed only of particles having a primary particle diameter of 10 nm or more, or may be composed only of particles having a primary particle diameter of 5 nm or more. That is, this step may be a step of preparing dispersion B2 by dispersing a mixed liquid containing ceramic particles β having a primary particle diameter of 10 nm or more or a primary particle diameter of 5 nm or more and an average primary particle diameter of 20 nm or more, a binder, and a dispersion medium until the value obtained by dividing the average secondary particle diameter of the ceramic particles β by the average primary particle diameter of the ceramic particles β is 1 or more and 10 or less. The particle diameter of the ceramic particles B1 may be the same as that of the ceramic particles β, but as long as the ratio of ceramic particles β / ceramic particles α in the composition is 1 or more and 20 or less, the ceramic particles B1 may contain particles with a primary particle diameter of less than 5 nm or less than 10 nm. The average primary particle size of the ceramic particles B1 is 20 nm or more, may be 30 nm or more, or may be 40 nm or more. The upper limit of the average primary particle size of the ceramic particles B1 may be, for example, 10 μm or less, 1 μm or less, 500 nm or less, or 100 nm or less, as long as adhesion to the substrate is obtained. The content of ceramic particles B1 in dispersion liquid B2 is not particularly limited as long as the ceramic particles B1 can be dispersed in the amount, and may be, for example, 1% by mass or more and 50% by mass or less, 5% by mass or more and 45% by mass or less, or 10% by mass or more and 40% by mass or less.

[0039] The binder may be the same as that described above. The content of the binder in the dispersion liquid B2 is not particularly limited as long as the value obtained by dividing the average secondary particle size of the ceramic particles B1 by the average primary particle size of the ceramic particles B1 is 1 to 10, and may be, for example, 0.1% by mass to 10% by mass, or 1% by mass to 8% by mass. The average secondary particle size of the ceramic particles B1 means the D50 value when the volumetric particle size distribution of the dispersion liquid B2 is measured, as described above. By dispersing the ceramic particles B1 until the value obtained by dividing the average secondary particle diameter of the ceramic particles B1 by the average primary particle diameter of the ceramic particles B1 is 1 or more and 10 or less, the ceramic particles A1 (ceramic particles α) can be uniformly present in the gaps between the ceramic particles B1 (ceramic particles β).

[0040] The dispersion medium is not particularly limited as long as it has a high affinity with the ceramic particles B1 and the binder, and examples thereof include water, methanol, ethanol, 1-propanol, 2-propanol, diacetone alcohol, furfuryl alcohol, ethylene glycol, hexylene glycol, terpineol, and other alcohols, methyl acetate, ethyl acetate, and other esters, diethyl ether, ethylene glycol monomethyl ether (methyl cellosolve), ethylene glycol monoethyl ether (ethyl cellosolve), ethylene glycol monobutyl ether (butyl cellosolve), diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, dioxane, tetrahydrofuran, and other ethers, acetone, methyl ethyl ketone, acetylacetone, acetoacetate, and other ketones, N,N-dimethylformamide, and other acid amides, toluene, xylene, and other aromatic hydrocarbons. Among these, alcohol is preferred from the viewpoint of high affinity with the binder. Ethanol is preferred from the viewpoint of ease of handling. The content of the dispersion medium can be the remainder of other components.

[0041] The method for dispersing the ceramic particles B1 in the dispersion medium is not particularly limited, but for example, a wet method is preferable, similar to the method for dispersing the ceramic particles A1 in the dispersion medium.

[0042] "Step of mixing dispersion A2 and dispersion B2" In this step, the dispersion liquid A2 and the dispersion liquid B2 are mixed so that the mass ratio of the ceramic particles B1 / ceramic particles A1 is 1 or more and 20 or less to obtain a composition. In order to adjust the viscosity and the porosity, a binder and an organic solvent may be added as appropriate. When the ceramic particles A1 contain particles having a primary particle diameter of 5 nm or more or 10 nm or more, or when the ceramic particles B1 contain particles having a primary particle diameter of less than 5 nm or less than 10 nm, the dispersion liquid A2 and the dispersion liquid B2 are mixed so that the mass ratio of the ceramic particles β / ceramic particles α is 1 or more and 20 or less. By mixing the dispersion liquid A2 and the dispersion liquid B2 in the above range, the ceramic particles A1 (ceramic particles α) can be uniformly present in the gaps between the ceramic particles B1 (ceramic particles β). The method for mixing the dispersion liquid A2 and the dispersion liquid B2 is not particularly limited, but for example, a propeller mixer or the like may be used.

[0043] Process for removing moisture In this step, when the composition contains moisture, the moisture is removed from the composition. If the composition contains moisture, the film-forming properties become poor, so moisture is removed from the resulting composition.

[0044] The method for removing water from the mixture is not particularly limited, and examples thereof include distillation using a rotary evaporator and adsorption dehydration using a molecular sieve.

[0045] According to the composition of the present embodiment, a composition capable of forming a porous film having excellent wettability and adhesion to a substrate and a low content of residual carbon can be obtained.

[0046] [Porous membrane] A porous film according to one embodiment of the present invention is a film formed from the composition according to the above embodiment.

[0047] The porous membrane of this embodiment preferably has an average pore size of 1 nm to 200 nm, more preferably 5 nm to 100 nm, and even more preferably 10 nm to 100 nm. If the average pore size is equal to or greater than the lower limit, gas and liquid permeability can be ensured. If the average pore size is equal to or less than the upper limit, when a composition containing another ceramic particle is applied on the porous membrane, the other ceramic particle can be prevented from penetrating into the pores and blocking the pores.

[0048] The porous membrane of the present embodiment has a porosity of 30% or more, preferably 50% or more, more preferably 52% or more, and even more preferably 55% or more. That is, the ratio of pores with an average pore diameter of 1 nm or more and 200 nm or less to the entire porous membrane of the present embodiment is preferably 50% or more, more preferably 55% or more, and even more preferably 60% or more. When the porosity is equal to or more than the lower limit, gas and liquid permeability can be ensured. The upper limit of the porosity may be 90% or less, 85% or less, or 80% or less.

[0049] The pore size and porosity of the porous membrane can be measured as follows. The composition of the above embodiment is applied onto a glass substrate, and the resulting coating is heat-treated to form a porous film. The obtained porous film is scraped off with the flat side of a metal spatula and peeled off from the glass substrate, and the peeled off material is measured by a nitrogen gas adsorption method using a specific surface area measuring device (trade name: Belsorp-miniII, manufactured by Microtrack-Bell Co., Ltd.) to calculate the pore size and pore volume by the BJH method from the adsorption isotherm measured by the nitrogen gas adsorption method. The average pore size is the pore size value at which the cumulative pore volume is 1 / 2 of the total pore volume from the pore size and pore volume calculated above. The porosity of the porous film is calculated from the obtained pore volume using the following formula (1). Porosity (%) = pore volume / (pore volume + 1 / ceramic particle density) × 100 (1) The unit of pore volume is "mL / g" and the unit of density is "g / cm 3 " In addition, when the types of ceramic particles α and ceramic particles β in the dispersion containing ceramic particles α and the dispersion containing ceramic particles β are different, the porosity of the porous film is calculated by the following formula (2). Ceramic particles α (density x (g / cm 3 )) and ceramic particles β (density y (g / cm 3 )) are contained in a mass fraction of X:Y and the pore volume is Z (mL / g), the porosity of the porous membrane is calculated by the following formula (2). Porosity (%)=Z / [Z+{X / (X+Y)} / x+{Y / (X+Y)} / y]×100 (2)

[0050] In the porous membrane of this embodiment, the proportion of pores having a pore diameter of 1 nm or more and 200 nm or less to the total pore volume is preferably 50% or more and 90% or less, the proportion of pores having a pore diameter of 5 nm or more and 100 nm or less to the total pore volume is more preferably 50% or more and 90% or less, and the proportion of pores having a pore diameter of 10 nm or more and 100 nm or less to the total pore volume is even more preferably 50% or more and 90% or less.

[0051] When the ratio of the pores having a pore diameter of 1 nm to 200 nm to the total pore volume of the porous membrane is 50% or more, the permeability of gas and gas can be ensured. Also, when the ratio of the pores having a pore diameter of 1 nm to 200 nm to the total pore volume is 90% or more, when another ceramic particle-containing composition or the like is applied and laminated on the porous membrane, the penetration of the other ceramic particles into the porous membrane and blocking the pores can be suppressed.

[0052] The proportion of the pores with a pore diameter of 1 nm or more and 200 nm or less in the total pore volume in the porous film can be measured by scraping the obtained porous film with the flat side of a metal spatula to peel it off from the glass substrate, and measuring the peeled material using a specific surface area measuring device (product name: Belsorp-miniII, manufactured by Microtrack-Bell) from the adsorption isotherm measured by the nitrogen gas adsorption method using the BJH method.

[0053] In the porous membrane of the present embodiment, the residual carbon content is preferably less than 1 mass%, more preferably 0.9 mass% or less, and even more preferably 0.7 mass% or less. When the residual carbon content is equal to or less than the upper limit, deterioration of the electrical and mechanical properties of the porous membrane due to the residual carbon can be prevented.

[0054] The residual carbon content in the porous membrane can be measured as follows. The composition of the above embodiment is applied onto a glass substrate, and the resulting coating is heat-treated to form a porous film. The obtained porous film is scraped off with the flat side of a metal spatula and peeled off from the glass substrate, and the weight loss of the peeled off material is measured with a thermogravimetric analyzer (TG / DTA6300, manufactured by Seiko Instruments Inc.), and the weight loss at 120°C to 800°C is taken as the weight loss of the residual carbon. That is, the weight A (g) of the peeled off material is measured with an electronic balance, and the weight loss B (g) at 120°C to 800°C is measured with TG-DTA, and the content of the residual carbon in the porous film is calculated as B / A×100.

[0055] "Method of manufacturing porous membrane" The method for producing the porous membrane of this embodiment will be described. The porous film of the present embodiment can be obtained by applying the composition of the above-described embodiment to the surface of a support such as a substrate, and then heat-treating the resulting coating.

[0056] The method of applying the composition to the surface of the support is not particularly limited and may be appropriately selected depending on the shape and material of the support. Examples of the method of applying the composition include wash coating, dip coating, screen printing, and other typical wet coating methods.

[0057] After the composition is applied, the thickness of the coating film may be adjusted by removing excess composition with compressed air or the like to a thickness greater than or equal to the thickness of the coating film.

[0058] A heat treatment is carried out to remove the binder contained in the coating film and form a porous ceramic film. The heat treatment temperature of the coating is not particularly limited as long as the binder is removed, but is preferably 300°C or higher and 800°C or lower, more preferably 400°C or higher and 700°C or lower, and even more preferably 450°C or higher and 600°C or lower. The heat treatment time of the coating film is preferably from 0.25 to 10 hours, and more preferably from 0.5 to 5 hours.

[0059] The atmosphere in which the coating film is heat-treated is not particularly limited as long as the binder is removed, and the heat treatment can be performed in any of the following atmospheres: an oxidizing atmosphere such as air; an inert atmosphere such as nitrogen, argon, neon, or xenon; or a reducing atmosphere such as hydrogen or carbon monoxide.

[0060] According to the porous film of the present embodiment, a porous film having excellent adhesion to the substrate and a low content of residual carbon can be obtained.

[0061] [Porous membrane with substrate] A substrate-attached porous membrane according to one embodiment of the present invention has a substrate and a porous membrane provided on at least one surface of the substrate, and the porous membrane is the porous membrane of the above-mentioned embodiment.

[0062] The substrate is not particularly limited as long as it is possible to form a porous film on at least one surface of the substrate. Examples of the substrate include porous ceramics, glass, and metals such as stainless steel and iron.

[0063] The substrate and the porous membrane may be made of the same material or different materials.

[0064] According to the substrate-attached porous membrane of the present embodiment, it is possible to obtain a substrate-attached porous membrane having a porous membrane with excellent adhesion between the substrate and the porous membrane and a low residual carbon content. EXAMPLES

[0065] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0066] [Example 1] ZrO2 particles A1 (manufactured by Sumitomo Osaka Cement Co., Ltd., equivalent to ceramic particles α) having an average primary particle diameter of 4 nm were dispersed in a 5% aqueous acetic acid solution so that the ZrO2 content was 20 mass % to prepare ZrO2 dispersion A2 of Example 1. A portion of the obtained ZrO2 dispersion A2 was taken and diluted with water so that the ZrO2 content was 1 mass% to prepare ZrO2 dispersion A3 for evaluation. The volumetric particle size distribution of this ZrO2 dispersion A3 for evaluation was measured using a particle size distribution meter (product name: SZ-100, manufactured by Horiba, Ltd.), and the results were D10 was 4.0 nm, D50 was 4.5 nm, D90 was 6.3 nm, and D50 / D90 was 0.71. The results are shown in Table 1.

[0067] Next, the ZrO2 particles and the ethyl cellulose were added to ethanol and mixed so that the content of ZrO2 particles B1 (manufactured by Daiichi Kigenso Kogyo Co., Ltd., equivalent to ceramic particles β) having an average primary particle diameter of 50 nm was 30 mass % and the content of ethyl cellulose as a binder was 3 mass % to prepare ZrO2 slurry dispersion B2 of Example 1. A portion of the obtained ZrO2 dispersion B2 was taken and diluted with ethanol so that the ZrO2 content was 1 mass% to prepare ZrO2 dispersion B3 for evaluation. The volumetric particle size distribution of this ZrO2 dispersion B3 for evaluation was measured using a particle size distribution meter (product name: SZ-100, manufactured by Horiba, Ltd.), and the results were D10 was 45 nm, D50 was 240 nm, D90 was 830 nm, and D50 / D90 was 0.29. The results are shown in Table 1. The average secondary particle size D50 of the ZrO2 dispersion B3 was divided by the average primary particle size of the ZrO2 particles B1 to obtain a value of 4.8.

[0068] A mixture was prepared by mixing 2 parts by mass of ZrO2 dispersion A2, 9 parts by mass of ZrO2 dispersion B2, and 16 parts by mass of ethyl cellulose in terms of ZrO2 solid content, and adding terpineol so that the total amount excluding the dispersion medium (water) contained in ZrO2 dispersion A2 and the dispersion medium (ethanol) contained in ZrO2 dispersion B2 was 100 parts by mass. Next, the water and ethanol in the mixture were removed using a rotary evaporator to obtain the composition of Example 1. The viscosity of the composition of Example 1 was measured using a viscometer (product name: MCR102, manufactured by Anton Paar) at room temperature (25°C) and a shear rate of 1 s -1 The measured value under these conditions was 930 Pa·s. The composition of Example 1 thus obtained was applied onto a glass substrate so that the film thickness after heat treatment would be 1 μm to form a coating film consisting of the composition of Example 1. The coating film was dried at 150° C. for 3 minutes and then heat-treated in air at 450° C. for 1 hour to obtain the porous film of Example 1.

[0069] [Example 2] A composition of Example 2 was obtained in the same manner as in Example 1, except that in the preparation of ZrO2 Dispersion A2, Dispersion A4 made with a 5% n-butyric acid aqueous solution was used instead of the 5% acetic acid aqueous solution. Using the obtained composition of Example 2, a porous membrane of Example 2 was obtained in the same manner as in Example 1. The volumetric particle size distribution of ZrO2 Dispersion A4 in Example 2 and the viscosity of the composition in Example 2 were measured in the same manner as in Example 1, and the results are shown in Table 1.

[0070] [Example 3] The composition of Example 3 was obtained in the same manner as in Example 1, except that in preparing ZrO2 dispersion A2, dispersion A5 made from ZrO2 particles (manufactured by Sumitomo Osaka Cement Co., Ltd., equivalent to ceramic particles α) having an average primary particle diameter of 3 nm was used. Using the obtained composition of Example 3, a porous membrane of Example 3 was obtained in the same manner as in Example 1. The volumetric particle size distribution of ZrO2 Dispersion A5 of Example 3 and the viscosity of the composition of Example 3 were measured in the same manner as in Example 1, and the results are shown in Table 1.

[0071] [Example 4] In terms of ZrO2 solid content, 1.1 parts by mass of ZrO2 dispersion A2 of Example 1, 4.8 parts by mass of ZrO2 dispersion B2 of Example 1, and 12.2 parts by mass of ethyl cellulose were mixed, and terpineol was mixed so that the total amount excluding the dispersion medium (water) contained in ZrO2 dispersion A2 and the dispersion medium (ethanol) contained in ZrO2 dispersion B2 was 100 parts by mass, except that the composition of Example 4 was obtained in the same manner as in Example 1. Using the obtained composition of Example 4, a porous membrane of Example 4 was obtained in the same manner as in Example 1. The viscosity of the composition of Example 4 was measured in the same manner as in Example 1. The results are shown in Table 1.

[0072] [Example 5] In terms of ZrO2 solid content, 5.6 parts by mass of ZrO2 dispersion A2 of Example 1, 23.8 parts by mass of ZrO2 dispersion B2 of Example 1, and 3.4 parts by mass of ethyl cellulose were mixed, and terpineol was mixed so that the total amount excluding the dispersion medium (water) contained in ZrO2 dispersion A2 and the dispersion medium (ethanol) contained in ZrO2 dispersion B2 was 100 parts by mass, except that the composition of Example 5 was obtained in the same manner as in Example 1. Using the obtained composition of Example 5, a porous membrane of Example 5 was obtained in the same manner as in Example 1. The viscosity of the composition of Example 5 was measured in the same manner as in Example 1. The results are shown in Table 1.

[0073] [Comparative Example 1] A composition of Comparative Example 1 was obtained in the same manner as in Example 1, except that in the preparation of ZrO2 Dispersion A2, Dispersion A6 made with ion-exchanged water was used instead of the 5% aqueous acetic acid solution. Using the obtained composition of Comparative Example 1, a porous membrane of Comparative Example 1 was obtained in the same manner as in Example 1. The volumetric particle size distribution of ZrO2 Dispersion A6 in Comparative Example 1 and the viscosity of the composition in Comparative Example 1 were measured in the same manner as in Example 1, and the results are shown in Table 2.

[0074] [Comparative Example 2] A composition of Comparative Example 2 was obtained in the same manner as in Example 1, except that in the preparation of ZrO2 Dispersion A2, Dispersion A7 made of ZrO2 particles (not corresponding to ceramic particles α) having an average primary particle diameter of 12 nm was used. That is, a composition of Comparative Example 2 not containing ceramic particles α having a primary particle diameter of less than 10 nm was obtained. Using the obtained composition of Comparative Example 2, a porous membrane of Comparative Example 2 was obtained in the same manner as in Example 1. The volumetric particle size distribution of ZrO2 Dispersion A7 of Comparative Example 2 and the viscosity of the composition of Comparative Example 2 were measured in the same manner as in Example 1, and the results are shown in Table 2.

[0075] [Comparative Example 3] A composition of Comparative Example 3 was obtained in the same manner as in Example 1, except that in the preparation of ZrO2 Dispersion A2, ZrO2 Dispersion A8 prepared with a 5% lauric acid-ethanol solution was used instead of the 5% acetic acid aqueous solution. Using the obtained composition of Comparative Example 3, a porous membrane of Comparative Example 3 was obtained in the same manner as in Example 1. The volumetric particle size distribution of ZrO2 Dispersion A8 of Comparative Example 3 and the viscosity of the composition of Comparative Example 3 were measured in the same manner as in Example 1, and the results are shown in Table 2.

[0076] [Comparative Example 4] In the preparation of the dispersion B2 of the embodiment 1, the composition of the comparative example 4 was obtained in the same manner as in the embodiment 1, except that the ZrO2 dispersion B4 prepared without using ethyl cellulose as a binder was used. Using the obtained composition of the comparative example 4, the porous film of the comparative example 4 was obtained in the same manner as in the embodiment 1. The volumetric particle size distribution of ZrO2 Dispersion B4 and the viscosity of the composition of Comparative Example 4 were measured in the same manner as in Example 1, and the results are shown in Table 2.

[0077] [Table 1]

[0078] [Table 2]

[0079] [evaluation] The porosity, residual carbon content, and adhesion were evaluated for the porous films obtained in Examples 1 to 5 and Comparative Examples 1 to 4. The results are shown in Table 3.

[0080] "Measurement of pore size and porosity" The obtained porous film was scraped off with the flat side of a metal spatula and peeled off from the glass substrate, and the peeled off material was measured by a nitrogen gas adsorption method using a specific surface area measuring device (trade name: Belsorp-miniII, manufactured by Microtrack-Bell Co., Ltd.) to calculate the pore volume by the BJH method from the adsorption isotherm. The porosity of the porous film was calculated from the obtained pore volume by the following formula (1). Porosity (%) = pore volume / (pore volume + 1 / ceramic particle density) × 100 (1) The density of ZrO2 particles is 5.7g / cm 3 It was calculated as:

[0081] "Measurement of residual charcoal" The obtained porous film was scraped off with the flat side of a metal spatula and peeled off from the glass substrate, and the weight loss of the peeled off material was measured with a thermogravimetric analyzer (TG / DTA6300, manufactured by Seiko Instruments Inc.), and the weight loss at 120°C to 800°C was taken as the weight loss of the residual carbon. That is, the weight A (g) of the peeled off material was measured with an electronic balance, and the weight loss B (g) at 120°C to 800°C was measured with TG-DTA, and the content of the residual carbon in the porous film was calculated as B / A×100.

[0082] "Adhesion measurement" An adhesive tape (manufactured by Nichiban, Cellotape (registered trademark)) with a width of 15 mm and a nominal adhesive strength of 4.7 N / 10 mm was applied to the porous membrane, and the adhesive tape was peeled off reliably in a direction at an angle of about 60° to the porous membrane (horizontal surface) in 0.5 to 1.0 seconds. If the force applied when the force was divided by the tape width was less than 5 N, the adhesive was evaluated as "Adhesion × (poor adhesion)" and if it was 5 N or more, the adhesive was evaluated as "Adhesion ○ (good adhesion)". A universal testing machine manufactured by Kyowa Interface Science Co., Ltd. was used to measure the adhesive strength.

[0083] [Table 3]

[0084] The results in Table 3 show that the porous films of Examples 1 to 5 have excellent adhesion to the substrate and contain a small amount of residual carbon. On the other hand, it was found that the porous films of Comparative Examples 1, 2 and 4 had poor adhesion to the substrate, and the porous film of Comparative Example 3 had a high content of residual carbon. From these results, it was confirmed that a composition obtained by mixing, in a specific ratio, a dispersion in which ZrO2 particles with an average primary particle size of less than 10 nm are dispersed in a carboxylic acid with a carbon number of less than 5 so that the average secondary particle size is 1 nm or more and 10 nm or less, and a dispersion in which ZrO2 particles with an average primary particle size of 20 nm or more are dispersed so that the average secondary particle size / average primary particle size is 10 or less, has excellent adhesion to the substrate when made into a porous film, a small residual carbon rate, and a porosity of 30% or more.

Claims

1. Ceramic particles α having a primary particle size of less than 10 nm; Ceramic particles β having a primary particle size of 10 nm or more; a carboxylic acid having less than 5 carbon atoms; Binder and an organic solvent, a ratio of the ceramic particles β to the ceramic particles α (ceramic particles β / ceramic particles α) is, in terms of mass ratio, 1 or more and 20 or less; The ceramic particles β have an average primary particle diameter of 20 nm or more.

2. The composition according to claim 1 , wherein the water content is 1% by weight or less.

3. The composition according to claim 1 , wherein the ceramic particles α and the ceramic particles β are an oxide containing zirconium.

4. A porous film which is a film formed from the composition according to any one of claims 1 to 3.

5. The porous membrane according to claim 4, having a porosity of 30% or more and a residual carbon content of less than 1% by mass.

6. A substrate; A porous membrane provided on at least one surface of the substrate, The porous membrane with a substrate, wherein the porous membrane is the porous membrane according to claim 4.

7. A method for producing the composition of claim 1, comprising the steps of: a step of dispersing a mixed liquid containing ceramic particles A1 having an average primary particle size of 1 nm or more and less than 10 nm, a carboxylic acid having a carbon number of less than 5, and a dispersion medium to prepare a dispersion A2 having an average secondary particle size of 1 nm or more and 10 nm or less; A step of dispersing a mixed liquid containing ceramic particles B1 having an average primary particle size of 20 nm or more, a binder, and a dispersion medium to prepare a dispersion B2; preparing a composition by mixing the dispersion A2 and the dispersion B2 in a mass ratio of the ceramic particles B1 to the ceramic particles A1 (ceramic particles B1 / ceramic particles A1) of 1 to 20, A method for producing a composition, wherein a value obtained by dividing the average secondary particle size of the dispersion liquid B2 by the average primary particle size of the ceramic particles B1 is 1 or more and 10 or less.

Citation Information

Patent Citations

  • Process for manufacture of separation film element

    JP1988274407A

  • Ceramic porous membrane, ceramic porous member using the same and production of these

    JP1998235172A